Pour une géographie de la relationalité.Repenser la solidarité territoriale urbaine avec les non-humains - Damien Marage; Anne Jégou (Bulletin de l’Association de Géographes Français)
As we enter the Anthropocene, the relationship of societies to themselves cannot be understood without including their relationship to nature. We need to rethink our societies and social change in terms of the relationship of human communities with other-than-human (OTH). To this end, we propose that a geography of relationality with OTH should emerge, and how this geography can serve projects of urban territorial solidarity. This relationality is constructed in three spatial dimensions, that of exposure and precarity, that of infrastructures and coexistence and finally that of assemblies and assemblages, the latter covering the field of governance. The urban environment thus acquires a heuristic value from this point of view. For working on relational quality objectives in the city implies raising the hope of changing mentalities by reinjecting meaning into the community, providing a framework and making a pluralist value judgement. We are beings in our own right, whether we are humans, animals or plants, first of all because we are in relationship.